PENINGKATAN PEMAHAMAN SISWA KELAS IV TENTANG SIKLUS AIR MELALUI PENGGUNAAN MEDIA DIORAMA DENGAN PENDEKATAN PROBLEM BASED LEARNING - Erlina Windy Ayu Safitri; Ulhaq Zuhdi; Ana Shofiya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the understanding of grade IV elementary school students about the concept of the water cycle. Students have difficulty visualizing and understanding the complex processes of the water cycle. This research will use diorama media and the Problem Based Learning (PBL) approach to improve student understanding. The research method used is classroom action research with two cycles. Each school consists of planning, implementation, observation, and reflection stages. Concept comprehension tests, observation of learning activities, and interviews were used to collect data. The subject of the study was a IV student of Manukan Kulon State Elementary School Surabaya. The results of the study show that the use of diorama media with the PBL approach can improve students' understanding of the water cycle. In the first cycle, the percentage of student learning completion increased to 65% and 85%, and student learning activities also increased, as shown by the increase in student enthusiasm and participation in learning. In the interview, students revealed that the PBL approach and diorama media helped them understand the concept of the water cycle in a more concrete and in-depth way. This study shows that grade IV students better understand the water cycle by using dioramas and problem-based learning approaches. This shows how important it is to use innovative learning media and apply a student-centered learning approach to improve the quality of education in primary schools.